(untitled) (Journal of actual problems of jurisprudence, 2019)
There were comprehensively considered the and peculiarities of the trasologi objects within the scientific criminalistics. It is possible to decide the questions of authentication and diagnostics of trasologii research of tracks of transport vehicles. On leave tracks moving parts it is possible to identify motion of transport. Key words: traces of automobile accessories, trace evidence, protector, motor Depot, criminalistics.